Melody tetrarchords in the Folklore Modern Iraqi songs (Al-Academy, 2017)
The study aimed .to identify on the melody tetrachords In the Iraqi Folklore song as mall as the melody tetracords is the basic in striation song if Iraqi Folklore so the researchers prepared their researchers from four chapters. In the first chapter of the researchers theoretical framework, included the research problem, which is determined by what is the melody tetra chords in the Iraqi Folklore songs. The research time limits were specific by year (2015-2016) then the first chapter ended with the terms mentioned in the title of research. The second chapter of the theoretical framework, included two subjects the first (Iraqi Folklore song) and the second subject included (melody tetra chords) then the third chapter deals with the research procedures that included the research the researchers adopted the descriptive analytical approach the research community included the (215) songs produced in the year (2015-2016) and 30 samples were selected in ten tonally of the research community. Finally chapter fore included the results of the research, conclusions recommendations proposals and of sources.